2015
DOI: 10.1007/s10853-015-9207-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical preparation and energy storage properties of nanoporous Co(OH)2 via pulse current deposition

Abstract: Nanoporous Co(OH) 2 films are electrochemically deposited on Ni foams by pulse current deposition for supercapacitor application. The pore size and density are controlled by reaction conditions including frequency modulation and reaction time. The morphology of the films is monitored by SEM, and the chemical composition and crystal structure are confirmed by XPS and XRD, respectively. The electrochemical performance of the Co(OH) 2 film is characterized by cyclic voltammetry and chargedischarge tests. The char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…4b, the two major peaks of Co 2p centered around 797 (Co 2p 1/2 ) and 781 eV (Co 2p 3/2 ) with a spin-energy separation of 16 eV indicated that Co existed in Co(OH) 2 form. 41,42 In the high resolution Ni 2p spectrum of Fig. 4c, two major peaks with binding energies at 855.8 and 873.6 eV are observed, corresponding to Ni 2p 3/2 and Ni 2p 1/ 2 , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…4b, the two major peaks of Co 2p centered around 797 (Co 2p 1/2 ) and 781 eV (Co 2p 3/2 ) with a spin-energy separation of 16 eV indicated that Co existed in Co(OH) 2 form. 41,42 In the high resolution Ni 2p spectrum of Fig. 4c, two major peaks with binding energies at 855.8 and 873.6 eV are observed, corresponding to Ni 2p 3/2 and Ni 2p 1/ 2 , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The multiplet splitting energy (∆E=16 eV) indicated that Co is existed as a Co(OH)2 version. [49][50] The O 1s spectrum and its fitted curves was shown in Fig. 3d, the main peak at binding energy of 531.3 eV corresponds to the Co-O-H bond, and the shoulder peak can be ascribed to structural water (532.8 eV).…”
Section: Resultsmentioning
confidence: 99%
“…The peaks were assigned to the electronic states of Co 2p 3/2 and Co 2p 1/2 , respectively. The multiplet splitting energy (Δ E = 16 eV) indicated that Co exists as a Co­(OH) 2 version. , The O 1s spectrum and its fitted curves are shown in Figure d; the main peak at binding energy of 531.3 eV corresponds to the CoOH bond, and the shoulder peak can be ascribed to structural water (532.8 eV). The shape and peak positions of the O 1s XPS spectrum are in good agreement with that of the previously reported Co­(OH) 2 . , …”
Section: Resultsmentioning
confidence: 99%
“…In the O 1 s spectrum of c‐CoSe 2 @Co(OH) 2 (Figure S8), the peaks locating at 529.9 and 531.2 eV are corresponded to CoO and structural water, 30,31 in which the occurrence of CoO may be due to dehydroxylation during drying. Importantly, the peak at 531.2 eV corresponds to Co(OH) 2 , which is also another important evidence for the existence of Co(OH) 2 32 …”
Section: Resultsmentioning
confidence: 87%
“…Importantly, the peak at 531.2 eV corresponds to Co(OH) 2 , which is also another important evidence for the existence of Co(OH) 2 . 32 In order to further understand the electronic structure of the materials, Co 0.85 Se and c-CoSe 2 @Co(OH) 2 were also characterized by ultraviolet photoelectron spectroscopy (UPS). The work functions of Co 0.85 Se and c-CoSe 2 @Co(OH) 2 are calculated to be 4.17 and 3.96 eV respectively, as shown in Figure 3C,D.…”
Section: Resultsmentioning
confidence: 99%